Suábios do Danúbio na Mata Atlântica do sul do Brasil: memória ambiental e paisagem - Klanovicz, Jo (Diálogos Latinoamericanos, 2015)
This article discusses the settlement process carried out by the Donauschwaben or Danube Swabians in Southern Brazil, from an environmental history point of view on landscape change in Atlantic Rainforest areas of Parana State. We believe that the group sought to build a new agricultural landscape based on its previous experience as farmers in pre-World War II Europe. In Brazil, Swabians had to negotiate their identity with natural conditions found in the west of the State of Parana. Immigrants tried to recreate their identity by the appropriatin of technical discourses to be defined as the regional progress promoters of modern agriculture and ethnic labor values. The research made use of technical reports, images and other documents produced by immigrants and local media to read this historical process.